A negative electrode material, a preparation method, a negative electrode sheet, a battery, and an electric device

CN122889714APending Publication Date: 2026-10-09SHENZHEN BTR NEW ENERGY TECH RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610930255.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-25
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0004]本发明提供了一种负极材料,旨在解决现有在包覆层中掺杂异质元素的手段难以再进一步提升负极材料的性能的技术问题

Benefits of technology

(1)本发明通过在石墨内核表面形成磷掺杂包覆层,并控制包覆层中磷元素在不同微区的含量差异,实现了磷元素在包覆层中的均匀分布,而非仅关注磷元素的掺杂量。具体而言,本发明任选5个1μm*1μm的区域进行磷元素EDS能谱采集并计算其质量分数,所述5个区域中的磷元素质量分数的相对标准偏差小于17%,而传统掺杂方案所测得的相对标准偏差普遍大于20%。首先,均匀分布的磷元素在硬碳包覆层中提供了大量均匀分散的储锂活性位点,有利于锂离子在包覆层中的充分储存;同时,均匀掺杂避免了因局部磷缺失导致的活性位点不足,使得材料的可逆容量得到充分发挥。其次,磷元素在硬碳包覆层中的均匀分布避免了局部磷富集所导致的界面副反应过度发生,同时确保了每个微区均具有适宜的活性位点密度,使得首次充放电过程中不可逆容量损失显著降低,也即提高了负极材料的首效。另外,磷元素在包覆层中的均匀分布确保了活性位点在包覆层中的均匀分散,锂离子在嵌入和脱出过程中无需经历因局部活性位点缺乏或拥堵导致的迂曲扩散路径,降低了电极极化,使得材料在高倍率下仍能保持良好的容量发挥。如表1,经过实验验证,本发明负极材料至少能够同步实现首次可逆容量达到387 mAh/g、首次库伦效率达到91.2%、2C倍率达到36.8%。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889714A_ABST
    Figure CN122889714A_ABST
Patent Text Reader

Abstract

The application provides a negative electrode material, a preparation method, a negative electrode sheet, a battery and an electric device, wherein the negative electrode material comprises a core and a coating layer, the core comprises graphite, the coating layer is coated outside the core, and the coating layer is doped with phosphorus elements; in an EDS energy spectrum analysis image of the negative electrode material, five 1*1 mu m regions are selected for phosphorus element EDS energy spectrum collection and calculation of mass fraction, and the relative standard deviation of the mass fraction of the phosphorus elements in the five regions is less than or equal to 17%. The negative electrode material solves the technical problem that the performance of the negative electrode material cannot be further improved by means of doping of heterogeneous elements in the coating layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of battery negative electrode material technology, and in particular relates to a negative electrode material, preparation method, negative electrode sheet, battery and power device. Background Technology

[0002] Graphite, with its excellent conductivity and cycle stability, is currently the mainstream anode material for lithium-ion batteries. However, its theoretical specific capacity is limited, and lithium dendrites are prone to precipitate on its surface under fast charging conditions, posing a safety hazard. Therefore, by using coating layers with larger spacing, lithium ions can be rapidly inserted and extracted, thereby improving capacity and rate performance. Furthermore, some existing technologies also dope the coating layer with heterogeneous elements (such as nitrogen, phosphorus, sulfur, etc.) to introduce defects and active sites, enhancing the adsorption capacity for lithium ions and improving the lithium storage activity of the material.

[0003] However, existing technologies typically focus only on the total content of doping elements in the coating layer and seek greater performance improvements such as capacity, rate capability, and first-efficiency by constantly trying different doping amounts. However, after years of exploration, the field has found that simply optimizing the doping amount can only improve the performance of anode materials to a limited extent, making it difficult to further improve the performance of anode materials. Summary of the Invention

[0004] This invention provides a negative electrode material that aims to solve the technical problem that existing methods of doping heterogeneous elements in the coating layer are insufficient to further improve the performance of negative electrode materials.

[0005] In a first aspect, embodiments of the present invention provide a negative electrode material, comprising: The kernel, comprising graphite; and, A coating layer, which covers the core and is doped with phosphorus; Specifically, in the EDS energy dispersive spectroscopy analysis image of the negative electrode material, five 1μm*1μm regions are randomly selected for EDS energy dispersive spectroscopy acquisition of phosphorus element and their mass fraction is calculated. The relative standard deviation of the phosphorus element mass fraction in the five regions is less than or equal to 17%.

[0006] In some alternative implementations, the kernel satisfies at least one of the following conditions: (1) The tap density of the core is 0.9 g / cm³. 3 above; (2) The D of the graphite 50 Particle size is 3~30 μm; (3) The graphite is selected from artificial graphite.

[0007] In some alternative implementations, the covering layer satisfies at least one of the following conditions: (1) The mass of the coating layer is 1wt% to 15wt% of the mass of the core; (2) The thickness of the coating layer is 50~500 nm; (3) The amount of phosphorus added in the coating layer is 0.1wt%~5wt%; (4) The coating layer is made from a biomass carbon source; the biomass carbon source includes lignocellulosic biomass; (5) The coating layer is also doped with nitrogen.

[0008] Secondly, embodiments of the present invention provide a method for preparing a negative electrode material, wherein the preparation steps of the negative electrode material include: Provides a biomass carbon source; The biomass carbon source was mixed with a phosphorus-containing compound solution and subjected to hydrothermal precarbonization treatment to obtain a phosphorus-doped hydrothermal carbon precursor. The phosphorus-doped hydrothermal carbon precursor is mixed and coated with a graphite liquid phase to form a composite precursor. The composite precursor is carbonized to obtain the anode material.

[0009] In some optional embodiments, the hydrothermal precarbonization treatment step includes: dispersing the biomass carbon source in an aqueous solution containing phosphorus compounds, mixing them evenly, and then keeping them at 180~280 ℃ for 4~24 h for reaction. After the reaction is completed, the solid product is collected to obtain a phosphorus-doped hydrothermal carbon precursor.

[0010] In some alternative embodiments, the aqueous solution of the phosphorus-containing compound satisfies at least one of the following conditions: (1) The mass concentration of the aqueous solution of the phosphorus-containing compound is 5%~30%; (2) The phosphorus-containing compound includes one or more of the following: phosphoric acid, phytic acid, sodium trimetaphosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, phosphorous acid, sodium phosphite, and sodium hypophosphite.

[0011] In some optional embodiments, the liquid phase mixing and coating step includes: dispersing the phosphorus-doped hydrothermal carbon precursor and graphite in a solvent at a mass ratio of 1:(5~20), adding a surfactant and / or crosslinking agent, and stirring and dispersing for 0.5~4 h to obtain a mixed slurry.

[0012] In some optional embodiments, after the liquid phase is mixed and coated, the mixed slurry is dried to obtain a powdered composite precursor; The drying method is spray drying or vacuum drying.

[0013] In some optional embodiments, the carbonization process includes: placing the composite precursor in an inert atmosphere, heating it to 800-1400 °C at a heating rate of 1-10 °C / min, and holding it at that temperature for 1-8 h to obtain the carbonized product.

[0014] In some optional embodiments, the biomass carbon source is purified before undergoing hydrothermal precarbonization treatment; the purification treatment method includes at least one of alkaline dissolution and acid precipitation method and steam explosion method.

[0015] In some optional embodiments, the preparation steps of the negative electrode material further include: pulverizing and sieving the obtained carbonization product to obtain the finished negative electrode material.

[0016] Thirdly, embodiments of the present invention provide a negative electrode sheet comprising the negative electrode material as described above.

[0017] Fourthly, embodiments of the present invention provide a battery including the negative electrode sheet as described above.

[0018] Fifthly, embodiments of the present invention provide an electrical device equipped with the battery described above.

[0019] The beneficial effects of the embodiments of the present invention are as follows: (1) This invention achieves uniform distribution of phosphorus in the coating layer by forming a phosphorus-doped coating layer on the surface of the graphite core and controlling the difference in phosphorus content in different micro-regions of the coating layer, rather than focusing solely on the doping amount of phosphorus. Specifically, this invention randomly selects five 1μm*1μm regions for EDS energy spectrum acquisition of phosphorus and calculates its mass fraction. The relative standard deviation of the phosphorus mass fraction in the five regions is less than 17%, while the relative standard deviation measured by traditional doping schemes is generally greater than 20%. First, the uniformly distributed phosphorus provides a large number of uniformly dispersed lithium storage active sites in the hard carbon coating layer, which is beneficial to the full storage of lithium ions in the coating layer. At the same time, uniform doping avoids insufficient active sites caused by local phosphorus deficiency, so that the reversible capacity of the material can be fully utilized. Second, the uniform distribution of phosphorus in the hard carbon coating layer avoids excessive interfacial side reactions caused by local phosphorus enrichment, while ensuring that each micro-region has a suitable active site density, which significantly reduces irreversible capacity loss during the first charge and discharge process, that is, improves the first efficiency of the anode material. Furthermore, the uniform distribution of phosphorus in the coating layer ensures the uniform dispersion of active sites. Lithium ions do not need to undergo tortuous diffusion paths due to a lack or congestion of local active sites during insertion and extraction, reducing electrode polarization and allowing the material to maintain good capacity performance at high rates. As shown in Table 1, experimental verification shows that the anode material of this invention can simultaneously achieve a first reversible capacity of 387 mAh / g, a first coulombic efficiency of 91.2%, and a 2C rate capability of 36.8%.

[0020] (2) The present invention adopts a liquid phase hydrothermal process to simultaneously complete three major processes: biomass pre-carbonization, in-situ phosphorus doping and carbon skeleton pre-crosslinking. Under the hydrothermal liquid phase environment, the phosphorus source can fully penetrate into the pores of the biomass carbon skeleton and anchor the carbon skeleton in the form of chemical bonds to achieve uniform doping. The simultaneous pre-crosslinking reaction solidifies the pore structure and interlayer spacing of the carbon precursor, which not only avoids the collapse of the pores of the subsequent high-temperature carbonization coating layer, but also solves the problem of easy peeling of the coating in the later stage. It realizes the integrated construction of phosphorus doping and hard carbon coating, ensures the consistency of material batches, and provides a stable process basis for improving the rate performance and cycle stability of the anode material. Attached Figure Description

[0021] To more clearly illustrate the solutions in this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0022] Figure 1 This is a SEM image of the phosphorus-doped biomass-based hard carbon-coated artificial graphite anode material prepared in Example 1 of this application. Detailed Implementation

[0023] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Furthermore, it should be understood that the specific embodiments described herein are only for illustration and explanation of the present invention and are not intended to limit the present invention. In the present invention, unless otherwise stated, directional terms such as "upper" and "lower" generally refer to the upper and lower positions of the device in actual use or operation, specifically the drawing directions in the accompanying drawings; while "inner" and "outer" refer to the outline of the device.

[0024] To address the technical problem of insufficient interfacial bonding strength between the coating layer and the graphite core in existing anode materials, which easily leads to delamination during charge-discharge cycles and affects battery performance, this application provides an anode material comprising: The kernel, comprising graphite; and, A coating layer, which covers the core and is doped with phosphorus; The phosphorus element is uniformly distributed within the coating layer.

[0025] In some embodiments, the coating layer is made of a carbon-based material. Examples of carbon-based materials include amorphous carbon, hard carbon, etc., and hard carbon is a further option.

[0026] Hard carbon materials possess large interlayer spacing and abundant closed-cell structures, exhibiting excellent sodium storage properties in sodium-ion batteries. When applied to lithium-ion batteries, they also possess higher lithium storage capacity potential compared to traditional graphite materials, making them a promising new type of carbon-based anode material. Existing technologies have attempted to use hard carbon to coat graphite to improve the electrochemical shortcomings of graphite anodes, but current coating modification schemes still have many technical defects that urgently need to be addressed. First, existing hard carbon coatings mostly use fossil-based carbon sources such as phenolic resin and polyacrylonitrile, which are non-renewable and have high carbon emissions during the preparation process, which does not conform to the green and low-carbon development trend of battery materials. Second, the interfacial bonding strength between conventional hard carbon coatings and graphite cores is weak. During long-term charge-discharge cycles, the coating is prone to peeling and delamination, leading to material structure collapse and rapid degradation of electrochemical performance. Third, traditional hard carbon coatings have a large specific surface area, which can easily aggravate electrolyte side reactions and reduce the initial coulombic efficiency of the battery. Fourth, although conventional biomass-based hard carbon raw materials are widely available, inexpensive, and green and renewable, their lithium storage capacity is relatively low, and without modification, they cannot meet the needs of high-rate and high-capacity batteries. Fifth, existing phosphorus-doped hard carbon coating processes cannot balance doping uniformity and coating structure stability. The coating thickness is difficult to control precisely. Too thick a coating will reduce the material's tap density and rate performance, while too thin a coating will not fully utilize the modification and efficiency-enhancing effects of phosphorus doping.

[0027] In hard carbon modification technology, heteroatom doping is a core and effective means to improve its electrochemical performance. Studies have found that phosphorus doping can effectively expand the interlayer spacing of hard carbon, optimize the electronic structure of the material, and introduce a large number of reversible lithium storage defects and electrochemical reaction active sites, which can significantly improve the specific capacity and rate performance of hard carbon materials. At present, the phosphorus-doped hard carbon coated graphite scheme still has obvious shortcomings: it is difficult to simultaneously achieve the uniformity of the distribution of dopants in the coating layer and the long-term stability of the coating structure; the balance between coating layer thickness control and modification effect and material tap density has not been effectively solved, making it difficult to synergistically leverage the performance advantages of both hard carbon and graphite materials.

[0028] This application studies and develops a phosphorus-doped biomass-based hard carbon-coated graphite anode material, with graphite as the core and phosphorus-doped biomass-based hard carbon coating as the shell. The phosphorus element is uniformly distributed in the coating layer through a hydrothermal pre-carbonization process. Phosphorus doping can expand the carbon layer spacing, introduce active sites, and improve lithium storage capacity and rate performance. Unlike existing technologies where phosphorus is only enriched on the surface of the coating layer with a low internal concentration, this application presents a uniform distribution of phosphorus within the coating layer. Phosphorus atoms can simultaneously exert a modifying effect throughout the entire coating layer: they uniformly expand the interlayer spacing within the carbon layer, avoiding structural inhomogeneity caused by excessively high local phosphorus concentrations on the surface, and allow lithium ions to obtain a rapid transport channel throughout the entire coating layer, preventing excessive local polarization. At the same time, uniform doping avoids the side reaction risks caused by phosphorus enrichment on the surface and eliminates the need to increase the coating layer thickness to ensure internal phosphorus content. Thus, while achieving a stable coating structure, it effectively balances the tap density and rate performance of the material, synergistically leveraging the dual advantages of graphite and hard carbon, and significantly improving the specific capacity and cycle stability of the composite anode material.

[0029] This application employs an X-ray energy dispersive spectroscopy (EDS) instrument equipped with a scanning electron microscope (SEM) to perform elemental surface scanning analysis on the material to characterize the distribution of phosphorus in the coating layer. Test conditions included: accelerating voltage approximately 4 kV, working distance approximately 5 mm, and magnification 5000x. Two-dimensional distribution images of phosphorus on the surface of the material particles were obtained through EDS mapping to observe the uniformity of phosphorus distribution in the coating layer. Under high-magnification scanning electron microscopy, unobstructed and relatively flat particle surface areas with particle sizes ranging from 5 to 25 μm were selected. Five 1 μm x 1 μm regions were selected using an equidistant grid sampling method. EDS spectra of phosphorus in each micro-region were collected, and the mass fraction was calculated. The relative standard deviation (RSD) was calculated based on the mass fraction (RSD = (standard deviation / average value) * 100%). A smaller RSD indicates a more uniform distribution of phosphorus.

[0030] In the EDS energy dispersive spectroscopy (EDS) images of the anode material in this application, five 1μm*1μm regions were randomly selected for phosphorus EDS energy dispersive spectroscopy acquisition, and their mass fraction was calculated. The relative standard deviation (RSD) of the phosphorus mass fraction in these five regions was less than or equal to 17%, while the RSD of traditional doping schemes was generally greater than 20%. Firstly, the uniformly distributed phosphorus provides a large number of uniformly dispersed lithium storage active sites in the hard carbon coating layer, which is beneficial for the full storage of lithium ions in the coating layer. Simultaneously, uniform doping avoids insufficient active sites due to local phosphorus deficiency, allowing the material's reversible capacity to be fully utilized. Secondly, the uniform distribution of phosphorus in the hard carbon coating layer avoids excessive interfacial side reactions caused by local phosphorus enrichment, while ensuring that each micro-region has a suitable active site density, significantly reducing irreversible capacity loss during the first charge-discharge process, thus improving the initial efficiency of the anode material. Furthermore, the uniform distribution of phosphorus in the coating layer ensures the uniform dispersion of active sites. Lithium ions do not need to undergo tortuous diffusion paths due to a lack or congestion of local active sites during insertion and extraction, reducing electrode polarization and allowing the material to maintain good capacity performance at high rates. As shown in Table 1, experimental verification shows that the anode material of this invention can simultaneously achieve a first reversible capacity of 387 mAh / g, a first coulombic efficiency of 91.2%, and a 2C rate capability of 36.8%.

[0031] It should be noted that although this invention uses EDS surface scanning to characterize the distribution of phosphorus on the coating layer surface, the two-dimensional characterization results can reflect the uniformity of phosphorus distribution throughout the three-dimensional space of the entire coating layer. This is because: firstly, in the preparation method of this invention, phosphorus is uniformly anchored to the biomass carbon framework through a hydrothermal reaction via chemical bonding, rather than simple physical mixing, fundamentally ensuring atomic-level uniform distribution of phosphorus in the carbon precursor; secondly, the dispersion effect of surfactants and the bridging effect of crosslinking agents during liquid-phase mixing enable the phosphorus-doped hydrothermal carbon precursor to be uniformly coated on the surface of artificial graphite particles, and the spray drying process can instantly solidify the droplets, preventing component migration or phase separation during drying, thereby ensuring the uniformity of phosphorus distribution in the thickness direction (i.e., in three-dimensional space) of the coating layer. Based on the above process characteristics, the relative standard deviation (RSD) of the phosphorus mass fraction in the EDS surface scanning results of the coating layer surface can effectively represent the uniformity of phosphorus distribution throughout the three-dimensional space of the entire coating layer.

[0032] In one embodiment, the kernel satisfies at least one of the following conditions: (1) The tap density of the core is 0.9 g / cm³. 3 The above can be listed as 0.9 g / cm³. 3 1.0 g / cm3 1.1g / cm 3 1.2 g / cm 3 1.3 g / cm 3 1.4 g / cm 3 1.5 g / cm 3 1.6 g / cm 3 1.7 g / cm 3 1.8 g / cm 3 1.9g / cm 3 2.0 g / cm 3 3.0 g / cm 3 4.0 g / cm 3 5.0 g / cm 3 wait; (2) The D of the graphite 50 The particle size is 3~30 μm; further selectable is 5~25 μm; even further selectable is 8~20 μm; examples include 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, etc. (3) The graphite is selected from artificial graphite.

[0033] This application selects D. 50 The particle size is 5~25 μm, and the tap density is ≥0.9 g / cm³. 3 Using graphite as the core ensures that the material has excellent intrinsic conductivity, structural stability and tap density, providing a basis for high cycle stability and rate performance of the anode material; the preferred particle size of 8~20 μm can balance ion transport efficiency and tap density, avoiding excessively small particle size leading to excessively high specific surface area and aggravated electrolyte side reactions, or excessively large particle size affecting rate performance.

[0034] The tap density referred to in this application refers to the mass per unit volume of the graphite material in the negative electrode core after tapping under specified conditions, and the unit is g / cm³. 3 The tap density is a core parameter determining the compaction performance and volumetric energy density of composite anode materials. A higher core tap density ensures that the coated material retains excellent compaction performance, preventing the coating layer from weakening the overall tap density, thereby guaranteeing the volumetric energy density of the battery and the stability of the electrode coating process. This application uses a tap density meter to test the tap density of the core material.

[0035] The D involved in this application 50Particle size (i.e., median particle size) refers to the particle size corresponding to a cumulative volume fraction of 50% in the particle size distribution of the graphite powder in the anode core, measured in μm. This particle size directly reflects the average size of the core particles and affects the specific surface area, ion transport path, and uniformity of the subsequent coating layer: excessively large particle size can lead to a longer lithium-ion transport path and a decrease in rate performance; excessively small particle size will increase the specific surface area and exacerbate electrolyte side reactions. A suitable D... 50 Particle size is crucial for balancing the rate performance, initial coulombic efficiency, and coating process stability of composite anode materials. This application uses a laser particle size analyzer to measure the D50 particle size of graphite.

[0036] In one embodiment, the covering layer satisfies at least one of the following conditions: (1) The mass of the coating layer is 1wt% to 15wt% of the mass of the core; it can be further selected as 3wt% to 10wt%; it can be listed as 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt%, 10wt%, etc.

[0037] (2) The thickness of the coating layer is 50~500 nm; it can be further selected as 100~400 nm; it can be listed as 100 nm, 120 nm, 140 nm, 160 nm, 180 nm, 200 nm, 220 nm, 240 nm, 260 nm, 280 nm, 300 nm, 320 nm, 340 nm, 360 nm, 380 nm, 400 nm, etc.

[0038] (3) The amount of phosphorus added in the coating layer is 0.1wt%~5wt%; it can be further selected as 0.5wt%~3wt%; it can be listed as 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2.0wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt%, 3.0wt%, etc.

[0039] (4) The coating layer is made from a biomass carbon source; the biomass carbon source includes lignocellulosic biomass; (5) The coating layer is also doped with nitrogen.

[0040] The amount of phosphorus doping in the coating layer is a key parameter affecting the modification effect: appropriate phosphorus doping can effectively improve the lithium storage capacity and rate performance of the material by expanding the carbon interlayer spacing and introducing lithium storage active sites; however, when the phosphorus content is too low, the above modification effect is difficult to fully realize; if the phosphorus content is too high, it is easy to cause problems such as uneven doping, decreased stability of the coating layer structure, and reduced tap density of the material, which will damage the battery performance. This application achieves the optimal balance between doping uniformity, structural stability and tap density by controlling the amount of phosphorus added in the coating layer within a specific range, which significantly improves the cycle life and rate performance of the battery.

[0041] This application prioritizes biomass raw materials as the carbon source to prepare a phosphorus-doped hard carbon coating layer, controlling the coating layer mass to be 1%~15% of graphite and the coating layer thickness to be 50~500 nm, thereby optimizing the performance and processability of the anode material. Biomass carbon source is green, renewable, and inexpensive; the appropriate coating layer thickness avoids excessive thickness reducing compaction performance and insufficient thickness failing to achieve the modification effect; more importantly, the coating layer ratio in this application can be as low as 3wt%~10wt%, still exhibiting good interfacial stability and lithium storage modification effect at low coating amounts. The core-shell boundary of the composite anode material is clear, with no interparticle adhesion or excess carbon source agglomeration during the coating process, resulting in high tap density and good batch consistency of the finished product, endowing the battery with excellent electrochemical performance.

[0042] The coating layer of this application can also be doped with nitrogen to form a phosphorus-nitrogen co-doped system. Nitrogen atoms can optimize the electronic structure of hard carbon, improve the conductivity of the material, and introduce more reversible lithium storage defects and reactive sites; phosphorus-nitrogen co-doping can synergistically expand the carbon interlayer spacing, significantly improve the interfacial reaction kinetics, reduce irreversible capacity loss, and improve the first coulombic efficiency, making the modification effect of the coating layer more comprehensive.

[0043] In one embodiment, the lignocellulosic biomass includes one or more combinations of coconut shells, walnut shells, apricot shells, straw, bamboo, sugarcane bagasse, rice husks, and corn cobs; the biomass carbon source may be coconut shells and / or walnut shells.

[0044] In this application, the coating layer is prepared from lignocellulosic biomass (coconut shells, walnut shells, apricot shells, straw, bamboo, bagasse, rice husks, corn cobs, etc.) as a biomass carbon source. Although there have been attempts in the industry to prepare hard carbon from lignocellulosic biomass, this type of carbon source has been difficult to directly use for graphite coating modification due to its inability to melt, which has become an industry challenge. This application uses a hydrothermal pre-carbonization process to convert it into a dispersible hydrothermal carbon precursor, breaking through the limitation of carbon source type. This not only realizes the high-value utilization of agricultural waste, but also utilizes its unique fibrous structure and hierarchical pores to provide more lithium ion storage sites and transport channels. Compared with the dense structure after carbonization of traditional small molecule carbon sources, it is more conducive to improving the specific capacity and rate performance of the material. The resulting anode material has a higher reversible lithium storage capacity and first coulombic efficiency compared with traditional fossil-based hard carbon (represented by petroleum pitch and coal tar).

[0045] This application also provides a method for preparing a negative electrode material, wherein the preparation steps of the negative electrode material include: Provides a biomass carbon source; The biomass carbon source was mixed with a phosphorus-containing compound solution and subjected to hydrothermal precarbonization treatment to obtain a phosphorus-doped hydrothermal carbon precursor. The phosphorus-doped hydrothermal carbon precursor is mixed and coated with a graphite liquid phase to form a composite precursor. The composite precursor is carbonized to obtain the anode material.

[0046] In one embodiment, the biomass carbon source is purified before undergoing hydrothermal precarbonization; the purification process includes at least one of alkaline dissolution and acid precipitation, and steam explosion.

[0047] The alkali dissolution and acid precipitation method involved in this application refers to the process of crushing biomass raw materials, dissolving and removing most of the impurities such as lignin and hemicellulose through alkali treatment to obtain purified cellulose components, followed by acid precipitation to precipitate purified cellulose, and then washing and drying to obtain purified biomass carbon source raw materials. This method can effectively remove ash and non-carbon impurities from biomass, improve the purity of the final carbon source, and reduce the negative impact of impurities on electrochemical performance.

[0048] In one embodiment, the specific operation of the alkali dissolution and acid precipitation method includes: crushing the biomass raw material into 2-5 mm particles, placing it in a 5-15% sodium hydroxide solution with a solid-liquid ratio of 1:(5-10), stirring at 90-105 °C for 3-5 h, filtering, and washing with deionized water until neutral; then placing the alkali-treated biomass raw material particles in an 8-14% hydrochloric acid solution, stirring at 70-85 °C for 1-3 h, filtering, and washing with deionized water until neutral.

[0049] The steam explosion method involved in this application refers to placing biomass raw materials in a high-temperature, high-pressure, closed environment, allowing water vapor to fully penetrate into the internal pores of the biomass. Subsequently, the system pressure is instantly reduced, and the explosion effect of the high-pressure water vapor inside destroys the original dense fibrous structure of the biomass, achieving component decomposition and loosening of the fibrous skeleton. At the same time, some hemicellulose and lignin impurities are removed, increasing the specific surface area and reactive sites of the raw materials. This method can efficiently deconstruct the dense structure of natural biomass, facilitating the uniform penetration of phosphorus-containing compounds into the interior of the biomass, providing a structural basis for achieving uniform phosphorus doping. At the same time, the process is simple, green and environmentally friendly, with no large amount of chemical reagent residues, meeting the requirements of green preparation.

[0050] In one embodiment, the purified biomass carbon source is dried, pulverized, and passed through a 50-300 mesh sieve to obtain a powdered biomass carbon source.

[0051] In one embodiment, the hydrothermal precarbonization treatment step includes: dispersing the biomass carbon source in an aqueous solution containing phosphorus compounds, mixing them evenly, and then keeping them at 180~280 ℃ for 4~24 h for reaction. After the reaction is completed, the solid product is collected to obtain a phosphorus-doped hydrothermal carbon precursor.

[0052] The hydrothermal pre-carbonization process employed in this application is a key step in achieving the coating of lignocellulose carbon sources and uniform phosphorus doping. This step involves dispersing the biomass carbon source in an aqueous solution containing phosphorus compounds and reacting it under hydrothermal conditions of 180–280 °C, simultaneously completing the hydrothermal carbonization of the biomass, uniform phosphorus doping, and pre-crosslinking of the carbon framework. Unlike the commonly used "coating before doping" process in existing technologies, this application adopts an innovative approach of "first uniformly doping the carbon source at the molecular level, then using it for coating." Through a liquid-phase hydrothermal environment, the phosphorus compounds and biomass precursors are brought into full contact at the molecular scale and react in situ, achieving a uniform distribution of phosphorus in the carbon precursor. This effectively overcomes the defects of traditional doping methods, such as uneven doping, poor stability of the coating layer structure, and decreased dispersibility.

[0053] The hydrothermal pre-carbonization process of this invention introduces abundant oxygen-containing functional groups and a unique mesoporous structure into the product, optimizing the doping effect of the coating layer. Simultaneously, this process eliminates the separate medium-temperature pre-carbonization step found in traditional processes, allowing for a direct one-step high-temperature carbonization treatment. While ensuring doping uniformity and coating layer structural stability, it significantly reduces energy consumption and shortens the production cycle, ultimately achieving superior results with "more uniform doping, thinner coating layer, and better electrochemical performance."

[0054] In one embodiment, the aqueous solution of the phosphorus-containing compound satisfies at least one of the following conditions: (1) The mass concentration of the aqueous solution of the phosphorus-containing compound is 5% to 30%; examples include 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, etc. (2) The phosphorus-containing compound includes one or more of the following: phosphoric acid, phytic acid (inositol hexaphosphate), sodium trimetaphosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, phosphorous acid, sodium phosphite, and sodium hypophosphite.

[0055] In one embodiment, the phosphorus-containing compound includes phytic acid.

[0056] This application first prepares a phosphorus-doped hydrothermal carbon precursor through hydrothermal pre-carbonization, then mixes it with graphite for liquid-phase coating. This allows the phosphorus-doped hydrothermal carbon precursor to be uniformly adsorbed on the surface of graphite particles. Subsequent carbonization yields a uniform and complete coating layer, achieving uniform and robust bonding of the coating layer and precise control of doping distribution. During the hydrothermal pre-carbonization process, phosphorus is uniformly anchored in the biomass carbon framework through chemical bonds, effectively overcoming the problem of uneven doping distribution in traditional physical mixing methods. Furthermore, by controlling the type and amount of phosphorus source, precise control of phosphorus doping can be achieved. Research shows that doped phosphorus atoms can form stable covalent bonds with carbon and oxygen atoms, providing more active sites for ion insertion and extraction, significantly improving the material's reaction kinetics.

[0057] This invention further selects phytic acid as a phosphorus-containing compound, which has the triple functions of phosphorus source, crosslinking agent and pore-forming agent. It realizes phosphorus doping, precursor crosslinking and curing and carbon material pore control in one step, which simplifies the preparation process, improves the high-value utilization efficiency of biomass resources and effectively reduces the environmental footprint of the material preparation process.

[0058] In one embodiment, the liquid phase mixing and coating step includes: dispersing the phosphorus-doped hydrothermal carbon precursor and graphite in a solvent at a mass ratio of 1:(5~20), adding a surfactant and / or crosslinking agent, and stirring and dispersing for 0.5~4 h to obtain a mixed slurry.

[0059] The liquid-phase mixing and coating involved in this application refers to the uniform dispersion of phosphorus-doped hydrothermal carbon precursor and graphite through a liquid medium. With the help of the interfacial modification effect of surfactants or the bonding effect of crosslinking agents, the phosphorus-doped hydrothermal carbon precursor is uniformly attached to the surface of graphite particles, completing the pre-assembly before coating. Unlike the problems of uneven coating and particle agglomeration that are prone to occur in traditional dry mechanical mixing, this method can achieve uniform and independent coating of individual graphite particles, reduce the adhesion between particles and the agglomeration of excess precursor, and ensure the uniformity of particle size distribution and tap density of the final negative electrode material. Further research revealed that parameter settings during the liquid-phase mixing and coating stage have a crucial impact on the modification effect: controlling the mass ratio of phosphorus-doped hydrothermal carbon precursor to graphite to be 1:(5~20) can precisely control the mass percentage of the coating layer within the optimal range of 1wt%~15wt%, ensuring a balance between the modification effect and the material compaction density; too short a stirring time will result in insufficient dispersion of the precursor, making it impossible to achieve uniform coating, while too long a stirring time will lead to energy waste. Controlling the stirring time to 0.5~4 h can balance coating uniformity and production efficiency.

[0060] In one embodiment, the crosslinking agent may include citric acid, maleic anhydride, glutaraldehyde, tartaric acid, glyoxal, boric acid, etc., and may be further selected as at least one of citric acid, maleic anhydride, and glutaraldehyde.

[0061] This application introduces a crosslinking agent during the liquid-phase mixing and coating stage to achieve chemical bonding bridging between the graphite matrix and the phosphorus-doped hydrothermal carbon precursor, thereby strengthening the interfacial bonding force of the core-shell structure. On the one hand, the crosslinking agent can undergo esterification and condensation reactions with active functional groups such as hydroxyl and carboxyl groups on the surface of the hydrothermal carbon precursor to form stable covalent bonds. On the other hand, the active groups on its molecular chain can react with oxygen-containing functional groups (such as hydroxyl and carboxyl groups) introduced on the graphite surface through pretreatment, or form C-C bonds through pyrolysis. This constructs a covalent connection bridge between the graphite matrix and the subsequently formed carbon coating layer, avoiding the delamination problem caused by the interface relying solely on physical adsorption bonding, and significantly improving the stability of the core-shell structure and the overall structural integrity of the material.

[0062] In one embodiment, the amount of crosslinking agent added is 2.0 wt% to 10.0 wt% of the hydrothermal carbon precursor; examples include 2.0 wt%, 3.0 wt%, 4.0 wt%, 5.0 wt%, 6.0 wt%, 7.0 wt%, 8.0 wt%, 9.0 wt%, 10.0 wt%, etc.

[0063] In one embodiment, the surfactant may include sodium dodecyl sulfate (SDS), sodium dodecylbenzene sulfonate (SDBS), polyvinylpyrrolidone (PVP), hexadecyltrimethylammonium bromide (CTAB), Tween, polyoxyethylene octylphenyl ether, P123 (PEO-PPO-PEO), etc., and may be further selected as at least one of sodium dodecyl sulfate, polyvinylpyrrolidone, and hexadecyltrimethylammonium bromide.

[0064] This application allows for the addition of surfactants during liquid-phase mixing and coating to further optimize the dispersion of phosphorus-doped hydrothermal carbon precursors and graphite in the solvent. By reducing solid-liquid interfacial tension, it minimizes particle aggregation and sedimentation, achieving a uniform and controllable distribution of the coating precursor on the graphite surface. Simultaneously, the molecular chains form a stable wetting layer at the graphite-precursor interface, providing uniform reaction sites for subsequent crosslinking reactions. This enhances the uniformity of the bonding between the coating layer and the graphite matrix, preventing uneven coating or detachment, and laying the foundation for the formation of a continuous and dense carbon coating layer during subsequent calcination.

[0065] In one embodiment, the amount of surfactant added is 1.0 wt% to 5.0 wt% of the hydrothermal carbon precursor; it can be further selected as 2.0 wt% to 4.0 wt%; examples include 2.0 wt%, 3.0 wt%, 4.0 wt%, etc.

[0066] In one embodiment, the solvent may include deionized water, ethanol, ethylene glycol, isopropanol, etc., and may further be deionized water and / or ethanol.

[0067] In one embodiment, when nitrogen is also doped in the coating layer, a nitrogen source is added during the liquid-phase mixing coating stage to achieve phosphorus-nitrogen co-doping coating; the nitrogen source may include one or more combinations of melamine, urea, dicyandiamide, ammonium chloride, and ethylenediamine.

[0068] In one embodiment, the amount of nitrogen source added is 2wt% to 10wt% of the biomass carbon source mass; examples include 2.0wt%, 3.0wt%, 4.0wt%, 5.0wt%, 6.0wt%, 7.0wt%, 8.0wt%, 9.0wt%, 10.0wt%, etc.

[0069] In one embodiment, after the liquid phase is mixed and coated, the mixed slurry is dried to obtain a powdered composite precursor.

[0070] In one embodiment, the drying method is spray drying or vacuum drying.

[0071] Based on the hydrothermal pre-carbonization liquid-phase mixing coating process of this application, a novel coating method suitable for biomass (especially non-meltable biomass) carbon source and pre-doped carbon source is further combined with spray drying process. This combined process can uniformly disperse and coat phosphorus-doped hydrothermal carbon precursor on graphite surface, effectively avoiding the problems of particle adhesion and uneven coating that are easy to occur in traditional melt coating process, and significantly improving the uniformity and structural stability of coating layer.

[0072] The spray drying involved in this application refers to atomizing a mixed slurry into fine droplets through an atomizer and then entering a drying chamber where the drying process is rapidly completed in high-temperature hot air. This allows the uniformly dispersed phosphorus-doped hydrothermal carbon precursor to be deposited evenly on the surface of graphite particles, resulting in a composite precursor with good dispersibility and uniform coating. This process avoids particle agglomeration and adhesion during drying, ensuring batch consistency and tap density of the final product. At the same time, the process can be continuously produced and is suitable for large-scale industrial preparation.

[0073] In one embodiment, the specific operation of the spray drying includes: conveying the mixed slurry to the spray drying equipment through a peristaltic pump, setting the inlet temperature to 200~240 ℃, the outlet temperature to 70~90 ℃, and the atomizing disc rotation speed to 10000~30000 rpm, to obtain a powdered composite precursor.

[0074] The vacuum drying involved in this application refers to drying under negative pressure below atmospheric pressure, which can lower the boiling point of the solvent in the mixed slurry, allowing the solvent to evaporate quickly at a lower temperature. This avoids premature carbonization and agglomeration of the precursor during high-temperature drying, making it easier to obtain a composite precursor with good dispersibility and uniform coating. It is especially suitable for small-batch laboratory preparation scenarios and is simple and convenient to operate.

[0075] In one embodiment, the carbonization process includes: placing the composite precursor in an inert atmosphere and heating it to 800-1400 °C at a heating rate of 1-10 °C / min and holding it at that temperature for 1-8 h to obtain the carbonized product.

[0076] The heating rate can be listed as 1 ℃ / min, 2 ℃ / min, 3 ℃ / min, 4 ℃ / min, 5 ℃ / min, 6 ℃ / min, 7 ℃ / min, 8 ℃ / min, 9 ℃ / min, 10 ℃ / min, etc.

[0077] The heating temperatures can be listed as 800 ℃, 900 ℃, 1000 ℃, 1100 ℃, 1200 ℃, 1300 ℃, 1400 ℃, etc.

[0078] The heat preservation time during the carbonization process can be listed as 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, etc.

[0079] This application eliminates the need for a separate medium-temperature pre-carbonization step in traditional processes after hydrothermal pre-carbonization, directly employing a one-step high-temperature carbonization to complete the preparation of the anode material. Existing processes often result in severe pyrolysis of the carbon precursor, damage to the coating layer structure, and severe adhesion between graphite particles, making it difficult to balance structural integrity and electrochemical performance. Based on hydrothermal pre-carbonization, this application achieves uniform densification of the coating layer by controlling specific heating rates, carbonization temperatures, and holding times. This avoids structural defects caused by rapid pyrolysis while ensuring the interfacial bonding strength between the phosphorus-doped carbon layer and the graphite matrix. Ultimately, this significantly improves the cycle stability and rate performance of the anode material while reducing production energy consumption and shortening the preparation cycle.

[0080] The carbonization process involved in this application refers to further carbonizing the phosphorus-doped hydrothermal carbon precursor under a high-temperature inert atmosphere, removing non-carbon heteroatoms such as hydrogen and oxygen, forming a phosphorus-doped hard carbon coating layer with high electrical conductivity, and promoting the reaction between the carbon precursor and the active sites on the graphite core surface to form a stable chemical bond connection, thereby obtaining a finished anode material with a clear core-shell structure and a strong interfacial bond.

[0081] The inert atmosphere referred to in this application is a gaseous atmosphere that does not chemically react with carbon precursors or graphite matrix. This atmosphere can prevent the carbon material from undergoing oxidation during high-temperature carbonization, ensuring the stable progress of the carbonization process and obtaining carbonized products with high purity and excellent electrochemical performance.

[0082] In one embodiment, the inert atmosphere may include, for example, nitrogen and / or argon.

[0083] In one embodiment, the preparation step of the negative electrode material further includes: pulverizing and sieving the obtained carbonization product to obtain the finished negative electrode material.

[0084] The crushing and sieving involved in this application refer to crushing the blocky or agglomerated carbonized products obtained from carbonization treatment into powder particles that meet the particle size requirements, and removing coarse particles that are too large and fine powder that are too small by sieving, so as to obtain a negative electrode material with uniform particle size distribution. This step can adjust the particle size of the final product to meet the requirements of electrode coating processing, ensure good processing performance and tap density of the material, and control the particle size distribution range to avoid the adverse effects of excessively wide particle size distribution on the electrochemical performance of the battery.

[0085] The process route of this invention takes into account both greenness and industrialization potential: it uses agricultural waste such as coconut shells and walnut shells as carbon sources to realize the high-value utilization of biomass resources; it selects natural phosphorus-containing compounds such as phytic acid, which have the functions of phosphorus source, crosslinking agent and pore-forming agent, to complete phosphorus doping and structural regulation in one step, simplifying the process and reducing the environmental footprint; the preparation process is continuous and controllable, and the equipment used in each process is the same as the equipment commonly used in the anode material industry, which has good prospects for industrial scale-up.

[0086] This application also provides a negative electrode sheet, comprising the negative electrode material as described above.

[0087] This application also provides a battery, including the negative electrode sheet as described above.

[0088] This application also provides an electrical device equipped with the battery described above.

[0089] The present application will be further described below through specific embodiments. Unless otherwise specified, the experimental materials used in the embodiments can be purchased from conventional biochemical reagent companies.

[0090] Example 1 This embodiment provides a negative electrode material, including a core and a coating layer covering the core; wherein: The core is made of artificial graphite; the tap density of the core is 1.08 g / cm³. 3 The D of the artificial graphite 50 The particle size is 11.2 μm; the artificial graphite is sourced from BTR New Energy Technology Research Institute Co., Ltd., and its model number is EA-1.

[0091] The coating layer is made of hard carbon and doped with phosphorus; the phosphorus is uniformly distributed within the coating layer; the mass of the coating layer is 5.0-10.0 wt% of the mass of the core; the thickness of the coating layer is 50-200 nm; the coating layer is made from coconut shells, a biomass carbon source.

[0092] This embodiment also provides a method for preparing a negative electrode material, the preparation steps of which include: S1. Biomass carbon source pretreatment The biomass carbon source, coconut shell, was purified using an alkaline dissolution and acid precipitation method. The specific steps were as follows: Coconut shells were crushed into 2-5 mm particles and placed in an 8% sodium hydroxide solution (solid-liquid ratio 1:8). The mixture was stirred at 100 °C for 4 h, filtered, and washed with deionized water until neutral. The alkaline-treated coconut shell particles were then placed in a 10% hydrochloric acid solution and stirred at 80 °C for 2 h. The mixture was then filtered and washed with deionized water until neutral. The purified biomass carbon source was dried at 100 °C for 12 h, pulverized, and passed through a 200-mesh sieve to obtain powdered biomass carbon source. S2. Hydrothermal precarbonization The powdered biomass carbon source obtained in step S1 was dispersed in a 15.0% phytic acid aqueous solution at a mass ratio of 1:5. After stirring evenly, the mixture was transferred to a hydrothermal reactor and subjected to hydrothermal pre-carbonization treatment at 220 °C for 12 h. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with deionized water, and dried at 100 °C for 24 h to obtain a phosphorus-doped hydrothermal carbon precursor. S3. Liquid-phase mixing and coating The phosphorus-doped hydrothermal carbon precursor obtained in step S2 was dispersed with graphite in deionized water at a mass ratio of 1:10. The surfactant polyvinylpyrrolidone (3.0wt%±1.0wt% of the hydrothermal carbon precursor) and the crosslinking agent citric acid (5.0wt%±2.0wt% of the hydrothermal carbon precursor) were added and stirred for 2 h to obtain a mixed slurry. S4. Spray drying The mixed slurry obtained in step S3 is spray-dried to obtain a powdered composite precursor. The specific operation is as follows: the mixed slurry is transported to the spray drying equipment by a peristaltic pump, the inlet temperature is set to 220℃, the outlet temperature is set to 80℃, and the atomizing disc speed is set to 20000rpm. S5. Carbonization treatment The composite precursor obtained in step S4 was placed in an inert atmosphere (nitrogen) and heated to 1150 °C at a heating rate of 5 °C / min and held for 3 h to obtain the carbonized product. S6. Post-processing The obtained carbonized products are pulverized (by rod milling) and sieved (325 mesh) to obtain the finished negative electrode material.

[0093] This application also provides a negative electrode sheet, the preparation steps of which include: The above-mentioned negative electrode material, conductive carbon black (SuperP), dispersant CMC, and binder (polyvinylidene fluoride, PVDF) were mixed in a mass ratio of 94:2:2:2. Water was added as a solvent, and the mixture was stirred and dispersed evenly in a high-speed mixer to obtain a negative electrode slurry with a solid content of 40%. The obtained negative electrode slurry was uniformly coated on the surface of a copper foil current collector. The coated electrode was placed in a 100 ℃ forced-air drying oven and dried for 45 min. Then, it was cut, rolled, and punched to form small discs. The small discs were then vacuum dried at 120 ℃ for 12 h to obtain the negative electrode sheet.

[0094] This application also provides a battery, the preparation steps of which include: Place the above-mentioned negative electrode sheet inside the positive electrode shell of the CR2016 battery, then drip in the electrolyte, stack the separator, drip in an appropriate amount of electrolyte, and then stack the lithium metal sheet, nickel mesh and stainless steel gasket in sequence. Then cover the negative electrode battery shell, and finally place it in the center of the sealing machine mold to press and seal it.

[0095] The electrolyte is 1.0 mol / L LiPF6, and the solvent is a mixture of EC:EMC:DMC in a ratio of 1:1:1.

[0096] Example 2 The difference between Example 2 and Example 1 is that the coating layer is also doped with nitrogen, while the rest is the same as in Example 1.

[0097] S2. Hydrothermal precarbonization The powdered biomass carbon source obtained in step S1 was dispersed in a 15.0% phytic acid aqueous solution at a mass ratio of 1:5. A nitrogen source (specifically melamine, added at 5 wt% of the coconut shell powder mass) was added and stirred until homogeneous. The mixture was then transferred to a hydrothermal reactor and subjected to hydrothermal pre-carbonization treatment at 220℃ for 12 h. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with deionized water, and dried at 100℃ for 24 h to obtain a phosphorus-doped hydrothermal carbon precursor. Example 3 The difference between Example 3 and Example 1 is that the biomass carbon source is walnut shells; the rest is the same as Example 1.

[0098] Example 4 The difference between Example 4 and Example 1 is that in step S2, the temperature is kept at 180 °C for 24 h; the rest is the same as in Example 1.

[0099] Example 5 The difference between Example 5 and Example 1 is that in step S2, the temperature is maintained at 280 °C for 4 h; the rest is the same as in Example 1.

[0100] Example 6 The difference between Example 6 and Example 1 is that the mass ratio of powdered biomass carbon source and phosphorus-containing compound aqueous solution in step S2 is 1:3; the rest is the same as in Example 1.

[0101] Example 7 The difference between Example 7 and Example 1 is that the mass ratio of powdered biomass carbon source to phosphorus-containing compound aqueous solution in step S2 is 1:10; the rest is the same as in Example 1.

[0102] Example 8 The difference between Example 8 and Example 1 is that the mass ratio of phosphorus-doped hydrothermal carbon precursor to graphite in step S3 is 1:5; the rest is the same as in Example 1.

[0103] Example 9 The difference between Example 9 and Example 1 is that the mass ratio of phosphorus-doped hydrothermal carbon precursor to graphite in step S3 is 1:20; the rest is the same as in Example 1.

[0104] Example 10 The difference between Example 10 and Example 1 is that the phosphorus stirring and dispersion time in step S3 is 0.5 h; the rest is the same as in Example 1.

[0105] Example 11 The difference between Example 11 and Example 1 is that the phosphorus stirring and dispersion time in step S3 is 4 hours; the rest is the same as in Example 1.

[0106] Example 12 The difference between Example 12 and Example 1 is that the heating rate in step S5 is 0.5 °C / min; the rest is the same as in Example 1.

[0107] Example 13 The difference between Example 13 and Example 1 is that the heating rate in step S5 is 10 °C / min; the rest is the same as in Example 1.

[0108] Example 14 The difference between Example 14 and Example 1 is that the D of the artificial graphite... 50 The particle size is 5 μm; otherwise, it is the same as in Example 1.

[0109] Example 15 The difference between Example 15 and Example 1 is that the D of the artificial graphite... 50 The particle size is 25 μm; otherwise, it is the same as in Example 1.

[0110] Example 16 The difference between Example 16 and Example 1 is that the D of the artificial graphite... 50 The particle size is 3 μm; otherwise, it is the same as in Example 1.

[0111] Example 17 The difference between Example 17 and Example 1 is that the D of the artificial graphite... 50 The particle size is 30 μm; otherwise, it is the same as in Example 1.

[0112] Example 18 The difference between Example 18 and Example 1 is that no crosslinking agent was added in step S3; the rest is the same as Example 1.

[0113] Example 19 The difference between Example 19 and Example 1 is that the amount of crosslinking agent added in step S3 is 2wt%; the rest is the same as in Example 1.

[0114] Example 20 The difference between Example 20 and Example 1 is that the amount of crosslinking agent added in step S3 is 10 wt%; the rest is the same as in Example 1.

[0115] Example 21 The difference between Comparative Example 21 and Example 1 is that the surfactant in step S3 is replaced with polyethylene glycol (PEG-400); the rest is the same as Example 1.

[0116] Example 22 The difference between Example 22 and Example 1 is that the crosslinking agent in step S3 is replaced with ethylenediaminetetraacetic acid (EDTA); the rest is the same as in Example 1.

[0117] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that no aqueous solution containing phosphorus compounds was added in step S2; that is, there was no phosphorus doping in the coating layer.

[0118] S2. Hydrothermal precarbonization The powdered biomass carbon source obtained in step S1 was dispersed in an aqueous solution at a mass ratio of 1:5. After stirring evenly, it was transferred to a hydrothermal reactor and subjected to hydrothermal pre-carbonization treatment at 220 °C for 12 h. After the reaction was completed, it was cooled to room temperature, filtered, washed with deionized water, and dried at 100 °C for 24 h to obtain a phosphorus-doped hydrothermal carbon precursor.

[0119] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the negative electrode material is first coated and then doped. Steps S2 and S3 are as follows: S2. Liquid-phase mixing and coating The phosphorus-doped hydrothermal carbon precursor obtained in step S2 was dispersed with graphite in deionized water at a mass ratio of 1:10. The surfactant polyvinylpyrrolidone (3.0wt%±1.0wt% of the hydrothermal carbon precursor) and the crosslinking agent citric acid (5.0wt%±2.0wt% of the hydrothermal carbon precursor) were added and stirred for 2 h to obtain a mixed slurry. S3. Hydrothermal precarbonization The powdered biomass carbon source obtained in step S1 was dispersed in a 15.0% (w / w) phosphoric acid aqueous solution at a mass ratio of 1:5. After stirring evenly, the mixture was transferred to a hydrothermal reactor and subjected to hydrothermal pre-carbonization treatment at 220°C for 12 h. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with deionized water, and dried at 100°C for 24 h to obtain a phosphorus-doped hydrothermal carbon precursor. The rest is the same as in Example 1.

[0120] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the biomass carbon source is lignin; the coating is carried out using a traditional coating method, and the specific steps for preparing the negative electrode material include: S1. Solid-phase mixed coating The lignin powder was dried at 100 °C for 12-24 h, passed through a 200-mesh sieve, and mixed with ammonium dihydrogen phosphate at a mass ratio of 1:0.3. The mixture was premixed using a ball mill, and then graphite was added (the mass ratio of the lignin and phosphorus source mixed powder to graphite was 15:100). The above materials were placed in a high-speed mixer and stirred at 300 rpm for 30 min to ensure that the components were mixed evenly, thus obtaining a solid-phase mixed precursor powder. S2. Carbonization treatment The solid-phase mixed precursor powder obtained in step S1 was placed in an inert atmosphere (nitrogen) and heated to 1150 °C at a heating rate of 5 °C / min and held for 3 h to obtain the carbonized product. S3. Post-processing The obtained carbonized products are pulverized (by rod mill) and sieved (325 mesh) to obtain the finished negative electrode material; The rest is the same as in Example 1.

[0121] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the spray drying in step S4 is replaced by drying in a blower drying oven, and the drying conditions are 100 °C for 24 h; the rest is the same as Example 1.

[0122] Test methods 1. Material Testing Methods 1) Characterization of phosphorus distribution within the coating layer Elemental surface area analysis (ESI) of the negative electrode materials prepared in the examples and comparative examples was performed using an X-ray energy dispersive spectroscopy (EDS) instrument equipped with a scanning electron microscope (SEM) to characterize the distribution of phosphorus within the coating layer. Test conditions: accelerating voltage 4 kV, working distance 5 mm, magnification 5000x. Two-dimensional distribution images of phosphorus on the surface of the material particles were obtained through EDS mapping to observe the uniformity of phosphorus distribution within the coating layer. Under high magnification scanning electron microscopy, unobstructed and relatively flat particle surface areas with particle sizes ranging from 5 to 25 μm were selected. Five 1 μm x 1 μm regions were selected using an equidistant grid sampling method. EDS spectra of phosphorus in each microregion were collected, and the mass fraction was calculated. The relative standard deviation (RSD) was calculated based on the mass fraction (RSD = (standard deviation / average value) * 100%). A smaller RSD indicates a more uniform distribution of phosphorus.

[0123] 2) Tap density: The tap density of the negative electrode materials in each embodiment and comparative embodiment was tested using a tap density meter.

[0124] 3) D 50 Particle size: The D particle size of the negative electrode materials in each embodiment and comparative example was measured using a laser particle size analyzer. 50 Particle size.

[0125] 2. Battery performance characterization The assembled CR2016 coin cell was tested using a Blue Electric test cabinet. Charge-discharge tests were performed on the coin cells, and the charge-discharge capacity was recorded and the capacity retention rate was calculated. The following parameters were recorded: initial reversible capacity (lithiation capacity at 0.1C in week 1), initial coulombic efficiency (=lithiation capacity at week 1 / lithiation capacity at week 1), and lithiation capacity at 2C discharge (= lithiation capacity at 2C / lithiation capacity at 0.2C). Table 1

[0126] By comparing Example 1 and Comparative Example 1, it can be found that the initial reversible capacity (374.0 mAh / g) and rate performance (2C / 0.2C=31.5%) of Example 1 are both higher than those of Comparative Example 1 (364.2 mAh / g and 29.3%, respectively). The reason is that the coating layer of Example 1 is doped with phosphorus. Phosphorus doping can expand the carbon interlayer spacing, optimize the electronic structure and introduce more lithium storage active sites, thereby improving the lithium storage capacity and rate performance of the material. In contrast, Comparative Example 1 did not undergo phosphorus doping, and the lithium storage capacity of the hard carbon coating layer itself is limited, resulting in insufficient modification effect.

[0127] By comparing Example 1 and Comparative Example 2, it can be found that the rate performance (31.5%) and RSD (8.2%) of Example 1 are better than those of Comparative Example 2 (29.8% and 34.5%). The reason is that Example 1 adopts the process sequence of "first phosphorus doping hydrothermal pre-carbonization, then liquid phase mixing and coating". Before coating, the phosphorus element is uniformly anchored in the carbon skeleton in the form of chemical bonds, and the distribution in the carbon coating layer is more uniform. In contrast, Comparative Example 2 adopts the sequence of "coating first, then doping". The phosphorus element is only enriched on the surface of the coating layer and is difficult to penetrate into the interior of the coating layer, resulting in uneven doping (RSD as high as 34.5%) and limited improvement in rate performance.

[0128] By comparing Example 1 and Comparative Example 3, it can be found that the first reversible capacity (374.0 mAh / g), rate performance (31.5%), and RSD (8.2%) of Example 1 are significantly better than those of Comparative Example 3 (359.5 mAh / g, 28.2%, and 29.8%). The reason is that Example 1 adopts a hydrothermal pre-carbonization + liquid phase mixing coating + spray drying process, which achieves uniform distribution of phosphorus in the coating layer and complete coverage of the coating layer; while Comparative Example 3 adopts solid phase mixing coating, where the phosphorus source and carbon source are only physically mixed, resulting in poor doping uniformity and insufficient bonding strength between the coating layer and the graphite core, leading to deterioration of electrochemical performance.

[0129] By comparing Example 1 and Comparative Example 4, it can be found that the rate performance (31.5%) and RSD (8.2%) of Example 1 are better than those of Comparative Example 4 (28.0% and 24.5%). The reason is that Example 1 uses spray drying, which can instantly solidify the droplets and avoid the migration or phase separation of components during the drying process, thus ensuring the uniform distribution of phosphorus in the coating layer. In contrast, Comparative Example 4 uses ordinary blower drying, during which the components in the droplets migrate with the solvent evaporation, resulting in the enrichment of phosphorus on the surface of the coating layer and its absence inside (RSD as high as 24.5%), thus reducing the rate performance.

[0130] Comparing Examples 1 and 2 reveals that, based on phosphorus doping, the introduction of nitrogen co-doping (Example 2) resulted in higher initial reversible capacity (377.5 mAh / g) and rate performance (33.2%) compared to Example 1 (374.0 mAh / g and 31.5%), with the RSD further reduced to 6.8%. This is because the introduction of nitrogen optimizes the electronic structure of hard carbon and improves the conductivity of the material, while phosphorus-nitrogen co-doping synergistically expands the carbon interlayer spacing, increases lithium storage active sites, and further improves the reaction kinetics of the material.

[0131] By comparing Examples 1 and 3, it can be found that when coconut shells (Example 1) and walnut shells (Example 3) are used as biomass carbon sources, both can achieve good coating effects and similar electrochemical performance (initial reversible capacities of 374.0 mAh / g and 369.8 mAh / g, respectively, and rate performance of 31.5% and 30.6%, respectively). This shows that the present invention has good applicability to different types of lignocellulosic biomass carbon sources, breaks through the limitations of traditional processes on the melting characteristics of carbon sources, and realizes the high-value utilization of various agricultural waste biomass carbon sources.

[0132] By comparing Examples 1 and 4 and 5, it can be found that good electrochemical performance can be obtained when the temperature setting of hydrothermal precarbonization is within the preferred range. The rate performance (32.9%) and RSD (8.5%) of Example 5 are basically equivalent to those of Example 1 (31.5%, 8.2%). The RSD (11.2%) of Example 4 is slightly higher but still at a good level. This shows that the hydrothermal precarbonization process of the present invention can effectively achieve phosphorus doping in a wide temperature window of 180~280℃ and has good process adaptability.

[0133] By comparing Examples 1 and 6 and 7, it can be found that effective phosphorus doping can be achieved in the mass ratio of biomass carbon source to phosphorus-containing compound solution within the range of 1:(3~10). Among them, the rate performance (32.6%) of Example 7 (mass ratio 1:10) is slightly better than that of Example 1 (31.5%), and the RSD (12.0%) of Example 6 (mass ratio 1:3) is relatively slightly higher. This indicates that appropriately increasing the amount of phosphorus-containing compound solution is beneficial to improving the uniformity of phosphorus doping, but even at a lower amount, a good modification effect can still be obtained.

[0134] Comparing Examples 1 and 8 and 9 reveals that a mass ratio of phosphorus-doped hydrothermal carbon precursor to graphite within the range of 1:(5~20) yields excellent overall performance. Example 8 (1:5, higher coating amount) exhibits superior capacity performance (387.5 mAh / g) and rate performance (36.8%), while Example 9 (1:20, lower coating amount) demonstrates higher tap density (1.07 g / cm³) and first coulombic efficiency (93.4%). This indicates that the present invention can flexibly meet different performance requirements by adjusting the coating amount.

[0135] By comparing Examples 1 and 10 and 11, it can be found that good coating effect can be achieved in the range of 0.5 h to 4 h of liquid phase mixing and stirring time. Among them, the RSD of stirring for 4 h (Example 11) is the best (7.0%), while the RSD of stirring for 0.5 h (Example 10) is slightly higher (16.2%), but uniform coating can still be achieved.

[0136] Comparing Examples 1 and 12 and 13 reveals that excellent electrochemical performance can be obtained within a carbonization heating rate range of 0.5℃ / min to 10℃ / min. Specifically, the rate performance (33.6%) and RSD (7.3%) of the product prepared under a heating rate of 0.5℃ / min (Example 12) are superior to or equivalent to those of Example 1. The performance of the product prepared under a heating rate of 10℃ / min (Example 13) is also essentially equivalent to that of Example 1, indicating that the present invention has a wide process window for carbonization heating rates.

[0137] By comparing Examples 1 and Examples 14, 15, 16, and 17, it can be found that graphite D50 with a particle size of 3 to 30 μm (Examples 1, 14, and 15) can achieve good overall performance. Among them, Example 14 (5 μm) shows excellent rate performance (38.2%), and Example 15 (25 μm) has a high first coulombic efficiency (93.0%) and tap density (1.12 g / cm³). When the particle size is set to 3 μm (Example 16) and 30 μm (Example 17), the phosphorus element can still be uniformly distributed in the coating layer.

[0138] Comparing Examples 1 and 18, 19, and 20 reveals that the introduction of the crosslinking agent has a positive impact on the uniformity of phosphorus distribution. Without the crosslinking agent (Example 18), the RSD was 14.8%. With the addition of the crosslinking agent, the uniformity was further improved. At 2 wt% (Example 19), the RSD decreased to 12.0%, at 5 wt% (Example 1) it further decreased to 8.2%, and at 10 wt% (Example 20) it remained at a good level of 12.8%. This demonstrates that the present invention can achieve uniform phosphorus doping even without the addition of a crosslinking agent, and the addition of an appropriate amount of crosslinking agent can further improve the uniformity and structural stability of the coating layer.

[0139] By comparing Examples 1 with Examples 21 and 22, it can be found that the RSD of Example 1 (8.2%) is significantly lower than that of Comparative Example 5 (17.5%) and Comparative Example 6 (16.8%). The reason is that Example 1 uses citric acid as a crosslinking agent and polyvinylpyrrolidone as a surfactant. Citric acid can promote the chemical crosslinking reaction between the hydrothermal carbon precursor and the graphite surface, and polyvinylpyrrolidone can optimize the dispersion effect of the precursor on the graphite surface. The synergistic effect of the three achieves the uniform distribution of phosphorus in the coating layer. In contrast, Comparative Example 5 uses EDTA as a crosslinking agent and Comparative Example 6 uses PEG-400 as a surfactant, neither of which can achieve the same degree of uniform doping effect, indicating that there is a better choice of type of crosslinking agent and surfactant.

[0140] A comprehensive comparison of the various embodiments and comparative examples shows that the present invention achieves uniform phosphorus distribution in the coating layer through a process combination of "biomass purification → hydrothermal pre-carbonization with simultaneous phosphorus doping → liquid-phase mixing and coating → spray drying → high-temperature carbonization". The RSD of each embodiment is as low as 6.8%~17%, significantly better than that of the comparative examples (24.5%~34.5%), indicating that the technical solution of the present invention has good universality and excellent doping uniformity under different process parameter conditions. In terms of electrochemical performance, the initial reversible capacity (364.0~387.5 mAh / g), initial coulombic efficiency (89.5%~93.4%), and rate performance (28.0%~38.5%) of each embodiment are generally better than those of the comparative examples (359.5~367.0 mAh / g, respectively). The values ​​of mAh / g, 91.2%~92.7%, and 28.0%~29.8% indicate that the technical solution of the present invention effectively improves the lithium storage capacity and rate performance of graphite anode materials while ensuring high tap density, and effectively solves the technical problems of uneven doping of coating layer, insufficient interface bonding strength, and poor rate performance in the prior art.

[0141] The embodiments of the present invention have been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only for the purpose of helping to understand the method and core ideas of the present invention. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention.

Claims

1. A negative electrode material, characterized in that, include: The kernel, comprising graphite; and, A coating layer, which covers the core and is doped with phosphorus; Specifically, in the EDS energy dispersive spectroscopy analysis image of the negative electrode material, five 1μm*1μm regions are randomly selected for EDS energy dispersive spectroscopy acquisition of phosphorus element and their mass fraction is calculated. The relative standard deviation of the phosphorus element mass fraction in the five regions is less than or equal to 17%.

2. The negative electrode material according to claim 1, characterized in that, The kernel satisfies at least one of the following conditions: (1) The tap density of the core is 0.9 g / cm³. 3 above; (2) The D of the graphite 50 Particle size is 3~30 μm; (3) The graphite is selected from artificial graphite.

3. The negative electrode material according to claim 1, characterized in that, The covering layer satisfies at least one of the following conditions: (1) The mass of the coating layer is 1wt% to 15wt% of the mass of the core; (2) The thickness of the coating layer is 50~500 nm; (3) The amount of phosphorus added in the coating layer is 0.1wt%~5wt%; (4) The coating layer is also doped with nitrogen.

4. A method for preparing a negative electrode material, characterized in that, The preparation steps of the negative electrode material include: Provides a biomass carbon source; The biomass carbon source was mixed with a phosphorus-containing compound solution and subjected to hydrothermal precarbonization treatment to obtain a phosphorus-doped hydrothermal carbon precursor. The phosphorus-doped hydrothermal carbon precursor is mixed and coated with a graphite liquid phase to form a composite precursor. The composite precursor is carbonized to obtain the anode material.

5. The preparation method according to claim 4, characterized in that, The hydrothermal precarbonization process includes: dispersing the biomass carbon source in an aqueous solution containing phosphorus compounds, mixing them evenly, and then keeping them at 180~280 ℃ for 4~24 h. After the reaction is completed, the solid product is collected to obtain a phosphorus-doped hydrothermal carbon precursor.

6. The preparation method according to claim 4, characterized in that, The aqueous solution of the phosphorus-containing compound satisfies at least one of the following conditions: (1) The mass concentration of the aqueous solution of the phosphorus-containing compound is 5%~30%; (2) The phosphorus-containing compound includes one or more of the following: phosphoric acid, phytic acid, sodium trimetaphosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, phosphorous acid, sodium phosphite, and sodium hypophosphite.

7. The preparation method according to claim 4, characterized in that, The liquid phase mixing and coating step includes: dispersing the phosphorus-doped hydrothermal carbon precursor and graphite in a solvent at a mass ratio of 1:(5~20), adding surfactant and / or crosslinking agent, stirring and dispersing for 0.5~4 h to obtain a mixed slurry.

8. The preparation method according to claim 4, characterized in that, After the liquid phase is mixed and coated, the mixed slurry is dried to obtain a powdered composite precursor; the drying method is spray drying or vacuum drying.

9. The preparation method according to claim 4, characterized in that, The biomass carbon source includes lignocellulose biomass; And / or, the biomass carbon source is purified before undergoing hydrothermal precarbonization treatment; the purification treatment method includes at least one of alkaline dissolution and acid precipitation method and steam explosion method.

10. A negative electrode sheet, characterized in that, Includes the negative electrode material as described in any one of claims 1 to 8.

11. A battery, characterized in that, Includes the negative electrode sheet as described in claim 10.

12. An electrical appliance, characterized in that, Assemble the battery as described in claim 11.